Efficacy and safety of empagliflozin (SGLT2 inhibitor) in Bangladeshi patients with type 2 diabetes mellitus - Wahiduzzaman, Miah; Yasmin, Abida; Shahriar Hossain, M.; Dhar, Rajib; Haider, M. Mahathir (International Journal of Research in Medical Sciences, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder requiring effective glycemic control to prevent complications. Methods: This 8-month, randomized, open-label, interventional, single centered trial enrolled 86 Bangladeshi patients with poorly controlled T2DM (HbA1c ≥7.5%) on various antidiabetic regimens. Participants received Empagliflozin 10mg/25mg in addition to their ongoing therapy. Follow-ups at 6 weeks and 6 months evaluated glycemic control, lipid profile, renal parameters and adverse effects. Based on clinical response, the dosage was increased to 25 mg in selected cases. Statistical analyses included paired t-tests and Wilcoxon Signed Rank tests for normally and non-normally distributed variables. Results: Hypertension was prevalent in 73.3% of cases, while chronic kidney disease (CKD), ischemic heart disease and dyslipidemia were observed in 12.8%, 14% and 37.2% of cases, respectively. Significant reductions in fasting blood sugar, postprandial blood sugar, systolic blood pressure (p<0.001 for all) and HbA1c (p<0.001) were observed at both 6-week and 6-month follow-ups. BMI reduction was significant at 6 months (p=0.03), while serum potassium increased significantly at both time points (p=0.02, p=0.01). Serum creatinine showed a significant decline at 6 months, while changes in LDL, triglycerides, HDL and total cholesterol were not statistically significant. Adverse effects were minimal, with 3.5% experiencing genital mycotic infections and 1.2% experiencing hypoglycemia. Conclusions: Empagliflozin effectively improved glycemic control and systolic blood pressure reduction with minimal adverse effects in Bangladeshi T2DM patients while increasing serum potassium level.